Asymmetric interactions between barley yellow dwarf virus -PAV and wheat dwarf virus in wheat - Armand, Thomas; Souquet, Marlène; Korn, Luâna; Gauthier, Kevin; Jacquot, Emmanuel (Frontiers in Plant Science, 2023)
The deciphering of the epidemiology of a plant virus has long been focused on the study of interactions between partners of one pathosystem. However, plants are exposed to numerous viruses which lead to frequent co-infection scenarios. This can change characteristics of virus-vector-host interactions and could impact the epidemiology of viral diseases. Barley yellow dwarf virus-PAV (BYDV-PAV; species: Luteovirus pavhordei; genus Luteovirus), wheat dwarf virus (WDV; genus Mastrevirus) and their respective vectors (BYDV-PAV: e.g. Rhopalosiphum padi and WDV: Psammotettix alienus) are commonly found in cereal fields. Wheat plants co-infected with BYDV-PAV and WDV have been reported from field surveys, although epidemiological outcomes of BYDV-PAV – WDV interactions in planta have not yet been studied. Experiments were carried out to evaluate and compare, through different competition scenarios (i.e. single- and co- (simultaneous and sequential) inoculations), the efficiency of BYDV-PAV and WDV to infect, to accumulate in and to be spread between wheat plants. Moreover, the impact of competition scenarios on the biological parameters of these two viruses was evaluated at different stages of the infection and with plants at different ages at inoculation. Results showed i) that these viruses achieve their infection cycle and their plant-to-plant transmission with different efficiencies and ii) BYDV-PAV – WDV interactions lead to different phenotypes ranging from antagonism to synergism. Finally, when these two viruses share a host, the nature and strength of virus-virus interactions varied depending on the order of virus arrival, stages of the infection cycle and plant age at inoculation. Precisely, the introduction (i.e. co- and sequential inoculation) and infection process (i.e. virus accumulation) of BYDV-PAV in a wheat benefit from the presence of WDV. For the latter, the sympatry with BYDV-PAV exerts opposite pressure on parameters involved in virus introduction (i.e. benefit during sequential inoculation) and spread (i.e. lower transmission efficiency and virus accumulation in co-infected plants). In the context of increased potential exposure of crops to insect vectors, this study participates in a better understanding of the impact of BYDV-PAV and WDV co-infections on biological and ecological parameters of the diseases induced by these viruses.